LECTOTYPIFICATION OF VIBURNUM BECCARII (ADOXACEAE). (1st March 2016) - Ranjan, Vinay; Srivastava, S. C.
Abstract : A lectotype of Viburnum beccarii Gamble (Adoxaceae) is proposed with an image of the material selected.